Performance analysis of multistage water gap membrane distillation system with economic evaluation. (5th February 2021) - Alawad, Suhaib M.; Khalifa, Atia E.; Antar, Mohamed A.
Highlights: Modeling of multistage water-gap membrane distillation (MSWGMD) system based on heat and mass transfer analysis. Consideration of water gap natural convection and module internal design details. Model validation with experimental results of the same module design. Comprehensive study of operating and design variables, energy analysis with focus on effects of number of stages. Freshwater production cost estimation and sensitivity analysis. Abstract: A theoretical modeling of multistage water gap membrane distillation (MSWGMD) process is presented to predict its performance with economic evaluation. The theoretical model is based on coupled heat and mass transfer analysis inside the water gap MD module and considering the effect of gap natural convection. The model is validated and used to study the variation of feed temperature, coolant temperature, and system productivity with the number of stages for the MD system with and without insulation. It is also used to predict the maximum and optimal number of stages that can be employed under specific operating conditions. In addition, the cost analysis of MSWGMD system is carried out. Results show that under the conditions of 20 °C coolant temperature, 50–90 °C feed temperature, 2.3 L/min feed and coolant flow rates, 4 mm gap thickness; the maximum number of stages that can be used is found to be 35 stages. In this case, the system productivity is about 5.2 L/h. It is also found that, by insulating pipe connections and the MD module, the total productivity increases by 36%. The optimum number of stages was found to be 15 stages, and the corresponding cost of freshwater production of the insulated multistage water gap MD process is about 3 $/m 3 .